2015
DOI: 10.1007/s11240-015-0733-3
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and shading regulate coloration and anthocyanin accumulation in the leaves of malus crabapples

Abstract: In many ornamental plants, anthocyanin accumulation in leaves is a critical determinant of foliage coloration. However, the mechanism by which photoperiod and shading affect coloration and anthocyanin accumulation in the leaves of woody plants is less clear. By examining the leaves and calli of crabapple (Malus spp.) cultivars with different leaf color characteristics, we analyzed the foliage coloration, flavonoid contents, and expression levels of anthocyanin biosynthetic genes and the McMYB10 transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Anthocyanin is responsible for the blue, purple and red colour of flower, fruits and leaves (Lu et al 2015). Monomeric anthocyanin reversibly change color with a change in pH.…”
Section: Anthocyanin Contentmentioning
confidence: 99%
“…Anthocyanin is responsible for the blue, purple and red colour of flower, fruits and leaves (Lu et al 2015). Monomeric anthocyanin reversibly change color with a change in pH.…”
Section: Anthocyanin Contentmentioning
confidence: 99%
“…Plants are classified according to photoperiodic responses into long-day (LD), in which flowering occurs when the day becomes longer than some crucial length, and short-day (SD), in which flowering occurs when the day becomes shorter [33]. Photoperiod also plays an important role in regulating the biosynthesis of secondary metabolites in plants [34], with longer photoperiods generally promoting anthocyanin biosynthesis [11, 49]. Nonetheless, some plants are able to activate the biosynthesis of anthocyanins in short photoperiod situations.…”
Section: Discussionmentioning
confidence: 99%
“…Pigments are key molecules in formation of the leaf colors [8,9]. Given that the color changes happened after 10 days, 30 days, and 50 days in leaves of CH, BM, and BO, we measured the contents of anthocyanin, chlorophyll a, chlorophyll b, and carotenoids in the three growth stages accordingly.…”
Section: Contents Of Pigments In Ch Leavesmentioning
confidence: 99%
“…Leaf color changes in plants are associated with the relative content alteration of pigments, including chlorophyll, carotenoids, anthocyanins, and their glycosides [5][6][7]. It has been reported that the abundant anthocyanin biosynthesis in the leaves and the excessive accumulation of anthocyanin-associated metabolites in the vacuole led to a red-leaf phenotype in ornamental plants, including Quercus coccifera and Malus crabapples [8,9]. To date, the mechanism involved in the determination of leaf color in Camellia plants, especially in C. japonica, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%